Duchenne muscular dystrophy disease severity impacts skeletal muscle progenitor cells systemic delivery - Saleh, Kholoud K.; Switzler, Corey; Hicks, Michael R.; Gane, Lily; Gibbs, Devin E.; Pyle, April D. (Frontiers in Physiology, 2023)
Duchenne muscular dystrophy (DMD) is caused by an out-of-frame mutation in the DMD gene that results in the absence of a functional dystrophin protein, leading to a devastating progressive lethal muscle-wasting disease. Muscle stem cell-based therapy is a promising avenue for improving muscle regeneration. However, despite the efforts to deliver the optimal cell population to multiple muscles most efforts have failed. Here we show that systemic delivery is inefficient and is affected by the microenvironment. We found overall that systemic delivery of skeletal muscle progenitor cells (SMPCs) was inefficient in all models. However, significantly less human SMPCs were detected in wt-NSG gastrocnemius muscle cross-sections, compared to both mdx-NSG and mdxD2-NSG. Human SMPCs were found to be detected inside blood vessels distinctly in healthy, dystrophic and severely dystrophic muscles, with prominent clotting identified in mdxD2-NSG after intra arterial (IA) systemic cell delivery. We propose that muscle microenvironment and the severity of muscular dystrophy to an extent impacts the systemic delivery of SMPCs and that overall systemic stem cell delivery is not currently efficient or safe to be used in cell based therapies for DMD.This work extends our understanding of the severe nature of DMD, which should be taken into account when considering stem cell-based systemic delivery platforms.